Zdarzenia i momenty. Schemat interpretacji nieewentystycznej - Grygianiec, Mariusz (Filozofia Nauki, 2011)
In the text Zdarzenia, rzeczy, procesy Zdzisław Augustynek argued against some versions of liberal reism that they are not able to deliver appropriate, non-circular definitions both of events and moments respectively. The main aim of the article is to show that the objection in question is not sound: indeed, we are vested with a procedure to find a way out from the indicated difficulty. In the text three forms of liberal reism are presented and their problems with the relevant definitions are analysed. Then the schematic method of defining the aforementioned categories is proposed and discussed. The presented considerations are crowned with the conclusion that in the light of the suggested reconstructions Augustynek’s pessimistic evaluation of reistic doctrines should not be seen as a correct one.